HIV-1 viral envelope protein gp41: An NMR investigation of dodecyl phosphocholine embedded gp41 reveals a dynamic pre-fusion intermediate conformation - Lakomek, Nils-Alexander (2014)
Human immunodeficiency viral (HIV-1) fusion is mediated by the viral envelope gp120/gp41 complex (ENVelope glycoprotein). After gp120 shedding, gp41 is exposed and elicits membrane fusion via a cascade of conformational changes. In contrast to pre-fusion and post-fusion conformation, little is known about any intermediate conformation. We report on a solution NMR investigation of homotrimeric HIV-1 gp41(27–194), comprising the transmembrane region and reconstituted in dodecyl phosphocholine (DPC) micelles. The protein is mainly α-helical but experiences internal dynamics on the nanosecond and micro-to millisecond time scale and transient α-helical behavior for certain residues in the N-terminal heptad repeat (NHR). Strong lipid interactions are observed, in particular for C-terminal residues of the NHR and imunodominant loop region connecting NHR and C-terminal heptad repeat (CHR). Our data indicate an extended conformation with features anticipated for a pre-fusion intermediate, presumably in exchange with a lowly populated post-fusion six-helical bundle conformation.